Beyond The “Social” In Social Media: Facebook As Communication Lifeline - S. Congjuico, Teresa (2015)
The Philippines’ geographic location combined with poor infrastructure and widespread incidence of poverty make its people highly vulnerable to risks. In the 2014 World Risk Report of the United Nations, the Philippines is ranked as the world’s second most at risk to disaster. It is also the third most exposed to natural calamities in the world. But the Philippines is also the “world’s most social nation”, with 21 percent and 20 percent of its 44.2 million Internet users actively and regularly using Facebook and Facebook Messenger, respectively. Collectively, Filipinos spend an average of nearly four hours of their time using social media daily for various “social reasons” which include personal networking, surveillance, entertainment, and simply filling up spare time. Of the 40 million active social media users, 36 million are mobile users. Growing at a rate of 50 percent per annum, these mobile users could reach 54 million by the end of year 2015, making it a key driving factor for social media penetration in the country. In recent months, local telecommunication giants have also made Facebook even more accessible by offering them to customers either absolutely free or very cheap. Wanting to be where the citizens are, local government officials have begun to tap the social medium to create their own online communities. Some have even integrated the social medium into their own risk communication network. Thus, Facebook is no longer just a social medium; it is now a communication lifeline. This paper explored the role of Facebook as a communication lifeline for the people of Cainta, Rizal during the onslaught of typhoon Mario on September 19, 2014. Specifically, this paper explored the role of Facebook as a crowdsourcing tool as well as looked into its affordances and limitations as a tool for risk management. For its framework, this study used Katz’ uses and gratification theory as updated by Thomas Ruggiero to incorporate the Internet and its technological affordances. The theory is a key communication theory which explains why people become involved in one type of mediated communication or another, and views audiences as active media users.